(untitled) (Tokyo, 1989)
This book introduce about tradition of christan humanism, the edeal of interdisciplinary studies and education.
Keywords: Giáo dục đại học,Education, Higher; Mục đích và mục tiêu,Aims and objectives; Nhật Bản,Japan